Overview of management and therapeutic advances in medullary thyroid cancer - Mark A Jara; Luciana Audi Castroneves (Endocrine Oncology)
Medullary thyroid carcinoma (MTC) is a rare cancer of the thyroid’s calcitonin-producing C cells. This review covers recent advances in MTC treatment, emphasizing surgical and systemic therapies. For localized MTC, surgery remains the primary and most effective treatment, with total thyroidectomy and lymph node dissection providing the highest potential for cure. However, prognosis worsens significantly with local and distant metastases, underscoring the importance of early diagnosis and intervention. MTC can be sporadic or hereditary, with the latter associated with germline RET proto-oncogene mutations linked to multiple endocrine neoplasia types 2A and 2B. Genetic discoveries have enabled preventive measures such as prophylactic thyroidectomy, increasing the cure rate of hereditary cases. Since 2011, systemic treatment options have expanded with multikinase inhibitors (MKIs), such as vandetanib and cabozantinib, and selective RET inhibitors such as selpercatinib and pralsetinib. MKIs extend progression-free survival in advanced cases by targeting tumor growth and angiogenesis but can cause off-target effects. RET inhibitors offer precision treatment for RET-mutated tumors, showing high efficacy and fewer side effects, though resistance to these inhibitors has emerged, and current research focuses on developing next-generation inhibitors to overcome these barriers. Effective MTC management, particularly given its rarity, benefits from specialized high-volume centers. Precision medicine, standardized therapy selection and ongoing research are essential for improving outcomes in both RET-positive and RET-negative MTC patients.